Functional MRI in optic neuritis: insights into cortical modulation and possible recovery mechanisms - McKyton, Ayelet; Abulafia, Ruth; Levin, Netta (Frontiers in Neurology, 2025)
Optic neuritis (ON) is an inflammatory, demyelinating optic neuropathy commonly associated with multiple sclerosis. It typically presents as monocular visual loss, with most visual functions recovering within several weeks. In addition to spontaneous remyelination, brain adaptation is thought to contribute to the recovery process. In this review, we discuss the role of functional MRI (fMRI) as a powerful tool for examining the cortical changes associated with ON. We explore studies that utilize a range of fMRI methodologies, highlighting their findings and implications for understanding cortical adaptation and recovery following peripheral visual loss. The review begins with traditional block-design fMRI protocols which assess activation strength in response to visual stimuli. It then shifts to analytical approaches that examine resting-state connectivity within the visual system. Advanced techniques, including population receptive field and connective field analyses, are also discussed, emphasizing their ability to probe neuronal spatial properties and detect changes following ON. Finally, we consider emerging fMRI methods that capture the temporal dynamics of cortical activity, underscoring their relevance for elucidating the time-dependent processes underlying cortical adaptation after ON.